Amino-functionalized resin-based nano zero-valent ruthenium-loaded composite material, preparation method thereof and application of composite material in catalytic reduction of bromate in water body

Through the electrostatic adsorption and in-situ catalytic reduction technology of amino-based functionalized resin-based nano-zero-valent ruthenium composite materials, the efficient removal of bromate ions in water is solved, and efficient, safe and controllable treatment effect is achieved, and the Treatment costs and secondary pollution risks.

CN119425789APending Publication Date: 2025-02-14ZHEJIANG UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411582319.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently remove bromate ions in water, and traditional methods have problems such as low treatment efficiency, harsh reaction conditions, high cost or possible secondary pollution.

Method used

The nano-zero-valent ruthenium composite material is used to convert bromate ions into harmless bromide through electrostatic adsorption and in-situ catalytic reduction, and the resin-based support is used to avoid the release of metal particles, realizing material regeneration and recycling. use.

Benefits of technology

It realizes efficient, safe and controllable removal of bromate ions in water, reduces treatment costs, avoids secondary pollution, and has good stability and durability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425789A_ABST
    Figure CN119425789A_ABST
Patent Text Reader

Abstract

The invention discloses an amido-functionalized resin-based nano zero-valent ruthenium-loaded composite material, a preparation method thereof and application of the amido-functionalized resin-based nano zero-valent ruthenium-loaded composite material in catalytic reduction of bromate in a water body, a matrix of the composite material is polystyrene resin with a propane diamine group, the matrix is spherical, the particle size distribution is 0.20-0.80 mm, and the pore size distribution is 1-50 nm; holes are uniformly distributed in the surface of the matrix, zero-valent ruthenium nanoparticles are uniformly distributed in the holes, the particle size of the zero-valent ruthenium nanoparticles is 2.0-30 nm, and the zero-valent ruthenium loading rate of the resin-based composite material is 0.5-5%. According to the invention, the resin-based zero-valent ruthenium composite material is used for reducing and removing bromate in the water body, and the composite material utilizes zero-valent ruthenium to enhance the reduction capability and selectivity of the reaction on the basis that a propylene diamine functional group has certain adsorption and reduction of bromate; tests show that when the pH value of a water body is 2.0-10.0, most bromate can be converted into bromide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sewage treatment and harmlessness, and in particular to an amine-functionalized resin-based nanometer zero-valent ruthenium composite material, a preparation method thereof, and an application thereof in catalytic reduction of bromate in water. Background Art

[0002] Bromate ion (BrO3 - ) is a type of disinfection byproduct produced during water treatment, which usually comes from bromide (Br - ) chemical reaction when a water source undergoes treatment processes such as ozone oxidation, persulfate oxidation or ferrate oxidation. Due to its chemical stability and high solubility in water, bromate ions are difficult to remove by traditional methods such as co-precipitation, and have been classified as a Class 2B potential carcinogen by the International Agency for Research on Cancer. In view of this, the World Health Organization (WHO) has set strict guideline limits for the content of bromate ions in drinking water, with a maximum limit of no more than 10 micrograms per liter (μg / L) to ensure public health. Therefore, the development and application of efficient technical means to remove bromate ions from contaminated water sources has become an important topic in the field of water treatment.

[0003] Common bromate removal technologies are mainly divided into three categories: physical separation, bioremediation and chemical reduction. Physical separation technologies, including activated carbon adsorption, ion exchange and membrane separation technologies, can capture bromate in adsorbents or concentrate it in wastewater. Although these methods can effectively reduce the concentration of bromate in water, they do not convert bromate into harmless substances, so further treatment is required to solve the problem of high concentrations of bromate. Bioremediation technology uses the action of microorganisms or enzymes to degrade bromate, but the efficiency of this method may be limited by the initial bromate concentration and the long biological treatment cycle. The chemical reduction method reduces bromate to harmless bromide through chemical reactions, which can achieve efficient decomposition of bromate in a shorter time and has obvious advantages in removal efficiency. Therefore, it is of application value and practical significance to develop a safe, controllable and cost-effective technology for eliminating bromate.

[0004] Zero-valent iron (nZVI) has shown great potential in the treatment of oxygen-containing anion pollutants due to its high reduction ability, but its application is limited by the oxidation problem caused by dissolved oxygen, which affects the reduction stability, and the sludge and corrosion products generated during the treatment process increase the complexity of subsequent separation and treatment. In view of the above challenges, catalytic reduction technology based on precious metals such as palladium and platinum has been proposed as an alternative. Ruthenium (Ru), also a platinum group metal, is also a transition metal. Its d orbital electrons are not fully filled, which enables it to accept or provide electrons in chemical reactions and participate in the catalytic process. In the reduction reaction, the ruthenium catalyst can adsorb and stabilize the intermediate species in the reaction, while providing the necessary electrons or hydrogen atoms. It is widely used in hydrogenation reactions, such as the hydrogenation reduction reaction of olefins, carbonyl compounds, aromatic carbocyclics and aromatic heterocyclic compounds with high regioselectivity and high stereoselectivity. At the same time, compared with other precious metal materials, the cost of ruthenium is relatively controllable (the price is about one-sixth of palladium). This cost advantage makes ruthenium have greater application potential in reactions such as catalytic reduction. However, highly active noble metal nanoparticles often face the problem of agglomeration, which causes their original high specific surface area and abundant active sites to be covered or destroyed, thus significantly reducing their catalytic activity. In addition, agglomeration will also make the dispersibility of nanoparticles worse, further affecting the utilization of their surface area. To overcome these obstacles, the key is to develop suitable carrier composites to optimize nanoparticle dispersion and prevent agglomeration.

[0005] The present invention innovatively proposes a method for preparing a functionalized resin-based nano-zero-valent ruthenium composite material, which successfully loads zero-valent ruthenium nanoparticles by grafting propylene diamine functional groups onto a chloromethylated polystyrene resin matrix. This design strategy achieves two major advantages: first, the excellent electron-donating effect of the propylene diamine group significantly enhances the catalytic reduction ability of zero-valent ruthenium to bromate, achieving the effective conversion from toxic bromate to harmless bromide; second, the zero-valent ruthenium particles are firmly anchored on the resin matrix with high mechanical strength, solving the problem of easy loss of particles and greatly improving the stability and durability of the material in water treatment applications. Furthermore, the composite material also has the ability to be regenerated and recycled, and can be desorbed and regenerated by treating with an alkali-salt mixture, which provides the possibility for cost control and resource recycling in practical applications. At present, literature searches show that there are no reports on methods for reducing and removing bromate from water bodies using functionalized resin-based nano-zero-valent ruthenium composite materials. Summary of the invention

[0006] In view of the technical problems existing in the prior art, the present invention aims to provide a functionalized resin-based nano-zero-valent ruthenium composite material, a preparation method thereof, and an application thereof in catalytic reduction to remove bromate ions from water. Specifically, the present invention provides a method for rapidly removing (BrO3- ) is converted into non-toxic bromide ions (Br - ), overcoming the problems of low efficiency, harsh reaction conditions, high cost or possible secondary pollution of traditional bromate ion treatment technologies (such as chemical reduction and biological treatment). At the same time, the resin-based zero-valent ruthenium composite material after the reaction can be regenerated with alkali solution and sodium borohydride and reused; loading zero-valent ruthenium on the resin carrier not only enhances the performance of reducing bromate in water, but also avoids the risk of secondary pollution caused by the release of metal into the water.

[0007] The amine-functionalized resin-based nano-zero-valent ruthenium composite material described above loads zero-valent ruthenium nanoparticles in the pores of the chloromethylated polystyrene resin exchange resin with propylene diamine groups. The composite material used in the present invention is a resin with propylene diamine functional groups [-NH(CH2)3NH2] on the skeleton of polystyrene-divinylbenzene, and nano-zero-valent ruthenium is loaded in its pores. Propylene diamine not only provides good dispersibility and stability, but also enhances the hydrophilicity and adsorption capacity of the material, which is beneficial to the uniform loading of nano-zero-valent ruthenium and the effective contact with bromate ions in the water body; secondly, the positively charged amine group preliminarily adsorbs the negatively charged bromate ions, increases the local concentration, and creates favorable conditions for the subsequent catalytic reduction reaction. In addition, the amine group of propylene diamine itself also has a certain reducibility. In the process of catalytic hydrogenation of nano-zero-valent ruthenium, the amine group can provide electrons to zero-valent ruthenium, promoting its catalytic activity. This electron transfer effect not only helps to accelerate the catalytic reduction reaction, but also helps to maintain the stability and activity of the catalyst. Zero-valent ruthenium has active chemical properties and good acid and alkali resistance. At the same time, the surface of ruthenium particles can catalyze the decomposition of nearby water molecules to produce active hydrogen (H*). Active hydrogen is a very active reducing species with strong reducing properties, which can reduce bromate in water to bromide.

[0008] The technical solution adopted by the present invention is as follows:

[0009] An amine-functionalized resin-based nano-zero-valent ruthenium composite material, wherein the matrix of the composite material is a polystyrene resin with a propylenediamine group, which is spherical, with a particle size distribution between 0.20 and 0.80 mm, and a pore size distribution between 1 and 50 nm; holes are evenly distributed on the surface of the matrix, and zero-valent ruthenium nanoparticles are evenly distributed in the holes, the particle size of the zero-valent ruthenium particles is 2.0 to 30 nm, and the zero-valent ruthenium loading rate of the resin-based composite material is 0.5 to 5%.

[0010] Furthermore, the zero-valent ruthenium loading rate of the resin-based composite material is 1.5-2.5%.

[0011] The resin-based zero-valent ruthenium composite material used in the present invention is based on the grafting of propylene diamine functional groups [-NH(CH2)3NH2] on the skeleton of chloromethylated polystyrene resin to load zero-valent ruthenium. Zero-valent ruthenium is very stable and has strong acid and alkali corrosion resistance. At the same time, the adsorbed hydrogen generated on the surface has good reducing ability and can reduce bromate in water to bromide.

[0012] The method for preparing the amine-functionalized resin-based nano-zero-valent ruthenium composite material comprises the following steps:

[0013] a) adding a chloromethylated polystyrene resin to an N,N-dimethylformamide swelling agent, subjecting the resin to swelling treatment for 18 to 24 hours, filtering off the swelling agent, performing solid-liquid separation to obtain the swollen chloromethylated polystyrene resin, and washing it with ethanol; then immersing the washed swollen resin in a mixed solution of propylene diamine and ethanol, heating the washed resin in a water bath at 40 to 60° C. to carry out an amine grafting reaction, filtering the resin, washing it with ethanol and water, and drying the resin to obtain a grafted propylene diamine resin;

[0014] b) soaking the propylene diamine resin in a hydrochloric acid solution containing an appropriate amount of ruthenium salt for 20 to 30 hours and placing it in a shaking table with a rotation speed of 100 to 200 rpm / min, filtering to obtain the propylene diamine resin impregnated with the loaded ruthenium ions, adding sodium borohydride solution dropwise to the aforementioned propylene diamine resin loaded with ruthenium ions to reduce the ruthenium ions to zero-valent ruthenium, and then performing solid-liquid separation and washing with ultrapure water, and drying to obtain a resin-based nano-zero-valent ruthenium composite material.

[0015] Furthermore, in the mixed solution of propylene diamine and ethanol in step a), the volume concentration of propylene diamine is 20-80%; the mass volume ratio of the chloromethylated polystyrene resin to the mixed solution is 1:10-30, the unit of mass is g, and the unit of volume is mL.

[0016] Furthermore, the concentration of the hydrochloric acid solution in step b) is 0.8-1.2 mol / L, and the ruthenium salt is at least one of ruthenium chloride, ruthenium nitrate and ruthenium sulfate.

[0017] The application of the amino-functionalized resin-based nano-zero-valent ruthenium composite material in catalytic reduction of bromate in water comprises the following steps:

[0018] (1) adjusting the pH of the bromate-containing water body to 2.0 to 10.0, filtering, and obtaining a filtrate;

[0019] (2) passing the filtrate obtained in step (1) through an adsorption tower filled with an amine-functionalized resin-based nano-zero-valent ruthenium composite material to obtain a treated water body;

[0020] (3) When the water body treated by the adsorption tower reaches the breakthrough point, the operation is stopped, and the composite material is first desorbed by using an alkali solution, and then the composite material is rinsed with water until it is neutral, and then reduced with a sodium borohydride solution to achieve regeneration of the composite material.

[0021] Further, in step (1), BrO3 - The mass concentration of bromate in the water is less than 100 mg / L, the mass concentration of other coexisting anions in the water is less than 5000 times the mass concentration of bromate ions, and the anions include one or more of chloride ions, nitrate ions, carbonate ions, sulfate ions and phosphate ions. The concentration of organic acids coexisting in the water is less than 100 mg / L, and the organic acids are humic acid or fulvic acid.

[0022] Furthermore, in step (2), the temperature of the filtrate passing through the composite material is 5 to 40° C., preferably 20 to 30° C., and the water outlet flow rate of the adsorption tower is 2 to 5 BV / h.

[0023] Furthermore, in step (3), the breakthrough point is when the mass concentration of bromate in the effluent is greater than 0.01 mg / L, and the BrO3 - The alkali solution is a NaOH aqueous solution with a mass percentage concentration of 0.1 to 4%; when the alkali solution passes through the amino-functionalized resin-based nano-zero-valent ruthenium composite material, desorption is performed at a flow rate of 1 to 5 BV / h at 10 to 40°C, and its volume usage is 10 to 50 times the filling volume of the composite material in the adsorption tower.

[0024] Furthermore, in step (3), the sodium borohydride solution is a sodium borohydride aqueous solution with a mass percentage concentration of 0.5 to 3%; when the sodium borohydride solution passes through the resin-based zero-valent ruthenium composite material, it is regenerated at a temperature of 10 to 40° C. and a flow rate of 1 to 5 BV / h.

[0025] Furthermore, in steps (2) and (3), a single-tower adsorption-desorption or multi-tower series adsorption-single-tower desorption operation mode is adopted.

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] (1) The method of the present invention uses a resin-based zero-valent ruthenium composite material to reduce and remove bromate in water. The composite material uses zero-valent ruthenium to enhance the reduction ability and selectivity of the reaction based on the fact that the propylenediamine functional group itself has a certain ability to adsorb and reduce bromate. Experiments have found that when the pH value of the water body is 2.0-10.0, most of the bromate can be converted into bromide.

[0028] (2) The resin-based zero-valent ruthenium composite material used in the method of the present invention can be regenerated with alkali solution and sodium borohydride solution after the reaction and recycled to reduce the processing cost.

[0029] (3) The resin-based zero-valent ruthenium composite material used in the method of the present invention loads zero-valent ruthenium on a resin carrier, thereby improving the reduction and selectivity performance while avoiding the release of metal particles into the water body to cause secondary pollution.

[0030] (4) The resin-based zero-valent ruthenium composite material used in the method of the present invention is simple to operate and consumes less energy. In the existing methods for reducing bromate in water, the metal composite material mainly uses itself as a medium and requires the addition of hydrogen, electricity or solar energy. The method of the present invention only requires the resin-based zero-valent ruthenium composite material to be put into the polluted water, which greatly simplifies the complexity of the operation and reduces the additional energy consumption.

[0031] On the one hand, the invention grafts propylenediamine functional groups with electron-donating ability, which significantly improves the catalytic reduction ability of zero-valent ruthenium particles to bromate, effectively converts toxic bromate into harmless bromide, and achieves harmless treatment. On the other hand, the invention fixes zero-valent ruthenium particles of different sizes on a resin matrix with good mechanical strength, effectively solving the problem of low mechanical strength and easy loss of particles, thereby significantly improving the stability and durability of the material in actual water treatment applications. At the same time, the composite material can be regenerated and recycled after desorption by an alkali-salt mixture. The composite material reduces and removes bromate in the water body. The treatment method of the invention is effective when the pH value of the water body is 2.0 to 10.0, and other coexisting Cl - PO4 3- 、CO3 2- 、SO4 2- When the mass concentration of competing substances such as organic acids is less than 100 times that of bromate ions, the bromate content of the effluent can still be reduced from less than 30 mg / L (in terms of BrO3 - to below 0.01 mg / L. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The morphology SEM and SEM-EDS images of the propylenediamine functionalized resin-based nano-zero-valent ruthenium composite material in Example 1 of the present invention;

[0033] Figure 2 It is the result of X-ray photoelectron spectroscopy after catalytic reduction of the propylenediamine functionalized resin-based nano-zero-valent ruthenium composite material in Example 1 of the present invention;

[0034] Figure 3 The catalytic reduction and removal effect of bromate by the resin-based nano-zero-valent ruthenium composite material prepared under different propylene diamine concentration conditions;

[0035] Figure 4 It is the catalytic reduction removal effect of bromate by different functional group resin-based nano-zero-valent ruthenium composite materials;

[0036] Figure 5 The catalytic reduction and removal effect of bromate by composite materials with different contents of nano-zero-valent ruthenium on resin matrix;

[0037] Figure 6 It is the catalytic reduction removal effect of bromate by resin-based composite materials with different nano-zero-valent metals. DETAILED DESCRIPTION

[0038] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention.

[0039] The chloromethylated polystyrene resin used in the examples of the present invention was purchased from Hangzhou Zhengguang Resin Co., Ltd.

[0040] Example 1

[0041] The preparation method of the resin-based nano-zero-valent ruthenium composite material is as follows:

[0042] 1) adding chloromethylated polystyrene resin to N,N-dimethylformamide swelling agent and subjecting to swelling treatment at room temperature for 20 hours;

[0043] 2) filtering out the swelling agent, separating the swollen chloromethylated polystyrene resin, washing it with ethanol, and then adding it to a propylene diamine-ethanol mixed solution with a volume fraction of 60% propylene diamine, the solid-liquid ratio of the chloromethylated polystyrene resin to the mixed solution is 1 g:20 mL, and carrying out a grafting reaction in a 50° C. water bath for 18 hours;

[0044] 3) After the reaction is completed, filter and wash with ethanol and water, and dry in a 55° C. thermostat for 12 hours to obtain a grafted propylene diamine resin;

[0045] 4) The obtained propylene diamine resin is soaked in 50 mL of 1M hydrochloric acid solution containing ruthenium chloride (the mass of Ru element in ruthenium chloride is 1.5% of the mass of propylene diamine resin), and placed in a constant temperature shaker at 25° C. and 100-200 rpm / min for 25 hours. Afterwards, the propylene diamine resin loaded with ruthenium ions is separated, and then a sufficient amount of 1.5% sodium borohydride aqueous solution is added dropwise, and ultrasonic treatment is performed for 40 minutes to reduce the ruthenium ions on the resin to zero-valent ruthenium, and then solid-liquid separation and ultrapure water washing are performed, and then drying is performed to obtain a resin-based nano-zero-valent ruthenium composite material.

[0046] The method for reducing and removing bromate in water by using the resin-based nano-zero-valent ruthenium composite material prepared in Example 1 has the following specific steps:

[0047] (1) 0.05 g of the resin-based nano-zero-valent ruthenium composite material was placed in a solution containing bromate (the cation bound to the anion was Na + , the same below); the concentration of bromate is 50mg / L, i.e. 0.39mmol / L (in terms of BrO3 - The volume of the solution is 100 ml, the pH value of the solution itself is between 6 and 7, and there is no need to adjust the pH. Place it in a constant temperature shaker at 25°C and shake for 24 hours.

[0048] (2) After the reaction, the supernatant of the solution was taken to measure the bromate ion and bromide ion. The result showed that the bromate ion concentration after the reaction was less than 1.5 mg / L (0.01 mmol / L), and the bromide ion concentration was about 22 mg / L (0.28 mmol / L). The removal rate of bromate was greater than 97%.

[0049] (3) Since the total molar concentration of bromine in step (2) is less than about 0.1 mmol / L, in order to prove that the resin-based zero-valent ruthenium composite material removes bromate by reduction rather than adsorption, the resin is separated from the solution and washed with ultrapure water into the solution. The solution is tested and analyzed to show that no bromate ions are present. The solution is then placed in a vacuum drying oven and dried to constant weight. The valence state of bromine adsorbed by the resin-based zero-valent ruthenium composite material is detected by X-ray photoelectron spectroscopy, as shown in FIG. Figure 2 As shown, almost all of the bromine elements adsorbed on the resin-based zero-valent ruthenium composite material exist in the form of bromide ions, so the bromate reduction rate should be the same as or close to the bromate removal rate, that is, the bromate reduction rate is close to 97% or greater than 97%.

[0050] (4) After the reaction in step (2) is completed, the resin-based zero-valent ruthenium composite material is washed with ultrapure water, and then 100 ml of a sodium hydroxide solution with a concentration of 0.1 mol / L is added for regeneration, and the solution is placed in a constant temperature shaker at 25±5°C and 180 rpm / min for 24 hours, and then washed with ultrapure water until the pH value of the solution is neutral. After solid-liquid separation, the resin is placed in a vacuum dryer for drying, and after drying, 100 ml of sodium borohydride solution (mass fraction of 1%) is added dropwise. After the addition is completed, ultrasonic treatment is performed for 45 minutes, and steps (1), (2) and (3) are repeated. The experimental results show that after five cycles, the bromate removal rate can still be maintained at more than 80%. Therefore, it is determined that the resin-based zero-valent ruthenium composite material is completely regenerated, and the regenerated resin-based zero-valent ruthenium composite material can be reused after the reaction.

[0051] 6) After ultrasonic treatment, solid-liquid separation was performed to obtain a resin-based zero-valent ruthenium composite material, which was washed with ultrapure water until there was no obvious reaction in the solution, and the obtained resin was filtered and vacuum dried to obtain a resin-based zero-valent ruthenium composite material. Scanning electron microscopy and energy spectrum ( Figure 1) shows the internal cross-sectional structure of the resin-based zero-valent ruthenium composite material and the distribution of propylene diamine functional groups and metal ruthenium. BET specific surface area detection shows that the average pore size of the resin-based zero-valent ruthenium composite material is 31.67nm and the average specific surface area is 37.11m 2 / g.

[0052] Example 2

[0053] The experimental steps of Example 2 are repeated in Example 1, except for the following two points:

[0054] First, in the preparation method of the resin-based nano-zero-valent ruthenium composite material, the volume fraction of propylenediamine in the propylenediamine-ethanol mixed solution in step 2) is replaced with 20%, 40%, 60%, 80% or 100% (i.e., pure propylenediamine), the solution volume remains unchanged, and the other conditions remain unchanged, and finally a resin-based nano-zero-valent ruthenium composite material prepared under different propylenediamine concentration conditions is obtained.

[0055] Second, a method for reducing and removing bromate from water using the resin-based nano-zero-valent ruthenium composite material prepared in Example 2 was repeated in the same manner as steps (1) to (2) of Example 1, with the only difference being that the bromate concentration in step (1) was increased to 100 mg / L, and the other conditions remained unchanged.

[0056] According to the method steps of Example 2, the catalytic reduction effect of the resin-based nano-zero-valent ruthenium composite material prepared under different propylene diamine concentration conditions is shown in FIG. Figure 3 ,like Figure 3 The removal rates of bromate by the resins prepared under the condition that the propylene diamine concentration is greater than or equal to 60% are basically the same. From the perspective of economic cost and performance, the resin prepared under the condition that the propylene diamine concentration is greater than or equal to 60% is selected.

[0057] Example 3

[0058] The experimental steps of Example 3 are repeated in Example 1, except for the following two points:

[0059] First, in the preparation method of the resin-based nano-zero-valent ruthenium composite material, the propylenediamine in the propylenediamine-ethanol mixed solution in step 2) is replaced with different functional group compounds with the same volume concentration, and the different functional group compounds are selected from methylamine, ethylamine, ethylenediamine, propylamine or propylenediamine. The solution volume remains unchanged, and the other conditions remain unchanged, and finally a resin-based nano-zero-valent ruthenium composite material modified with different functional groups is obtained.

[0060] Second, a method for reducing and removing bromate from water using the resin-based nano-zero-valent ruthenium composite material prepared in Example 3 was repeated in the same manner as steps (1) to (2) of Example 1, with the only difference being that the bromate concentration in step (1) was increased to 100 mg / L, and the other conditions remained unchanged.

[0061] According to the method steps of Example 3, the catalytic reduction and removal effect of bromate by the resin-based nano-zero-valent ruthenium composite material modified with different functional groups is shown in FIG. Figure 4 It can be seen that the propylene diamine resin-based zero-valent ruthenium composite material has the best removal effect on bromate. In comparison, the main reason why the resin with a single amine functional group has a poor effect may be the reduction in the number of amine groups and the strong hydrophobicity of the single amine functional group resin. The reason why the ethylene diamine resin is not as effective as the propylene diamine resin may be that the appropriate growth of the carbon chain is conducive to the transfer of electrons.

[0062] Example 4

[0063] The experimental steps of Example 4 are repeated in Example 1, except for the following two points:

[0064] First, in the preparation method of the resin-based nano-zero-valent ruthenium composite material, the ruthenium chloride content in the 50 mL 1M hydrochloric acid solution in step 4) is adjusted so that the mass of the Ru element in the ruthenium chloride is 0% (i.e., no ruthenium chloride is added), 0.5%, 1.0%, 1.5%, 2.0% or 2.5% of the mass of the propylenediamine resin, and the other conditions remain unchanged, and finally a resin-based nano-zero-valent ruthenium composite material with different ruthenium contents is obtained.

[0065] Second, a method for reducing and removing bromate from water using the resin-based nano-zero-valent ruthenium composite material prepared in Example 4 was repeated in the same manner as steps (1) to (2) of Example 1, with the only difference being that the bromate concentration in step (1) was increased to 100 mg / L, and the other conditions remained unchanged.

[0066] According to the method steps of Example 4, the catalytic reduction and removal effect of bromate by the resin-based nano-zero-valent ruthenium composite material with different ruthenium contents is shown in FIG. Figure 5 ,like Figure 5 The removal rates of bromate by the resins prepared under the condition that the metal ruthenium loading is greater than or equal to 1.5% are basically the same. From the perspective of economic cost and performance, the resin with a metal ruthenium loading of 1.5% is selected.

[0067] Example 5

[0068] The experimental steps of Example 4 are repeated in Example 1, except for the following two points:

[0069] First, in the preparation method of the resin-based nano-zero-valent ruthenium composite material, the obtained propylene diamine resin is immersed in 50 mL of 1M hydrochloric acid solution containing different metal chlorides (the mass of the metal element in the metal chloride is 1.5% of the mass of the propylene diamine resin), and the other conditions remain unchanged, and finally the resin-based nano-zero-valent ruthenium composite material with different metal loads is obtained. The different metal chlorides are chlorides of ruthenium, palladium, copper, cobalt or iron.

[0070] Second, a method for reducing and removing bromate from water using the resin-based nano-zero-valent ruthenium composite material prepared in Example 5 was repeated in the same manner as steps (1) to (2) of Example 1, with the only difference being that the bromate concentration in step (1) was increased to 100 mg / L, and the other conditions remained unchanged.

[0071] According to the method steps of Example 5, the catalytic reduction effect of bromate removal by the resin-based nano zero-valent ruthenium composite material with different metal loads is shown in Figure 6 ,like Figure 6 The shown propylenediamine resin-based zero-valent ruthenium composite material has the best removal effect on bromate.

[0072] Example 7

[0073] The same method as in Example 1 was used to treat bromate in water, except that the pH of the reaction was adjusted to 2, 3, 4, 5, 6, 7, 8, 9, and 10 (±0.03), respectively. The removal rates of bromate were all greater than 94%, and the bromate reduction rate was close to the bromate removal rate.

[0074] Example 8

[0075] The same method as in Example 1 was used to treat bromate in water, except that the temperature of the constant temperature shaker in step (1) was controlled at 10±5°C. The removal rate of bromate was greater than 90%, and the bromate reduction rate was close to the bromate removal rate.

[0076] Example 9

[0077] The same method as in Example 1 was used to treat bromate in water, except that the temperature of the constant temperature shaker in step (1) was controlled at 40±5°C. The bromate removal rate was 100%, and the bromate reduction rate was close to the bromate removal rate.

[0078] Example 10

[0079] The same method as in Example 1 was used to treat bromate in water, except that the initial concentration of bromate in step (1) was controlled at 1-30 mg / L, the removal rate of bromate could reach 100%, and the bromate reduction rate was close to the bromate removal rate.

[0080] Embodiment 11

[0081] The same method as in Example 1 was used to treat bromate in water, except that the initial concentration of bromate in step (1) was controlled at 30-70 mg / L, the removal rate of bromate was greater than 90%, and the bromate reduction rate was close to the bromate removal rate.

[0082] Example 12

[0083] The same method as in Example 1 was used to treat bromate in water, except that the initial concentration of bromate in step (1) was controlled at 70-100 mg / L, the removal rate of bromate was greater than 85%, and the bromate reduction rate was close to the bromate removal rate.

[0084] Embodiment 13

[0085] The same method as in Example 1 was used to treat bromate in water, except that in step (1), 8 mmol / L Cl was added. - The removal rates of bromate were all greater than 94%, and the bromate reduction rate was close to the bromate removal rate.

[0086] Embodiment 14

[0087] The same method as in Example 1 was used to treat bromate in water, except that in step (1), 8 mmol / L of NO3 was added. - The removal rates of bromate were all greater than 93%, and the bromate reduction rate was close to the bromate removal rate.

[0088] Embodiment 15

[0089] The same method as in Example 1 was used to treat bromate in water, except that in step (1), a final concentration of 4 mmol / L CO3 was added. 2- The removal rates of bromate were all greater than 90%, and the bromate reduction rate was close to the bromate removal rate.

[0090] Example 16

[0091] The same method as in Example 1 was used to treat bromate in water, except that SO4 with a final concentration of 8 mmol / L was added in step (1). 2- The removal rates of bromate were all greater than 92%, and the bromate reduction rate was close to the bromate removal rate.

[0092] Embodiment 17

[0093] The same method as in Example 1 was used to treat bromate in water, except that PO4 with a final concentration of 4 mmol / L was added in step (1). 3-The removal rates of bromate were all greater than 91%, and the bromate reduction rate was close to the bromate removal rate.

[0094] Embodiment 18

[0095] The same method as in Example 1 was used to treat bromate in water, except that HA with a final concentration of 50 mg TOC / L was added in step (1). The bromate removal rate was greater than 93%, and the bromate reduction rate was close to the bromate removal rate.

[0096] Embodiment 19

[0097] A treatment method for reducing and removing bromate in water using a resin-based zero-valent ruthenium composite material, the specific steps are as follows:

[0098] (1) Adjust the water body's bromate concentration to 0.2 mg / L, chloride ion and sulfate ion concentrations to 100 mg / L, and nitrate ion and carbonate ion concentrations to 30 mg / L. - Control the pH value between 6 and 7, filter and obtain a filtrate;

[0099] (2) 20 mL (about 10 g) of the resin-based zero-valent ruthenium composite material of Example 1 was placed in a jacketed glass adsorption column (Φ32×360 mm). The filtrate obtained in step (1) was passed through the adsorption column containing the resin-based zero-valent ruthenium composite material bed at a flow rate of 5 BV / h at 25±5°C to produce BrO3 - The concentration was reduced to below 10 ppb;

[0100] (3) When the breakthrough point is reached (BrO3 - The operation was stopped when the concentration was greater than 10ppb), and the processing capacity was about 2980BV. First, 1000mL of sodium hydroxide solution (the concentration of sodium hydroxide was 0.1mol / L) was passed through the resin bed at a flow rate of 1BV / h at a temperature of 25±5°C for regeneration, and then it was washed with ultrapure water until neutral for regeneration, and 1000mL of sodium borohydride solution (the mass percentage concentration of sodium borohydride was 1%) was added to pass through the resin bed at a flow rate of 1BV / h at a temperature of 25±5°C for regeneration, and then it was washed with ultrapure water. The overall regeneration rate of the composite material was >90%.

[0101] Embodiment 20

[0102] The same method as in Example 19 was used to treat bromate in water, except that in step (1), the pH value of the bromate-containing water was adjusted to 2.0±0.05. The experimental results showed that when the leakage point (BrO3 - When the concentration is greater than 10ppb, the operation is stopped and the treatment effect and treatment capacity remain basically unchanged.

[0103] Embodiment 21

[0104] The same method as in Example 19 was used to treat bromate in water, except that in step (1), the pH value of the bromate-containing water was adjusted to 10.0±0.05. The experimental results showed that when the leakage point (BrO3 - When the concentration is greater than 10ppb, the operation is stopped and the treatment effect and treatment capacity remain basically unchanged.

[0105] Embodiment 22

[0106] The same method as in Example 19 was used to treat bromate in water, except that in step (2), the temperature of the filtrate passing through the bed containing the adsorbent material was controlled to be 10±5°C. The experimental results showed that when the leakage point (BrO3 - When the concentration is greater than 10ppb), the operation is stopped and the treatment effect and treatment volume are slightly reduced.

[0107] Embodiment 23

[0108] The same method as in Example 19 was used to treat bromate in water, except that in step (2), the temperature of the filtrate passing through the bed containing the adsorbent material was controlled to be 40±5°C. The experimental results showed that when the leakage point (BrO3 - When the concentration is greater than 10ppb), the operation is stopped, and the treatment effect and treatment capacity are slightly increased.

[0109] Embodiment 24

[0110] The same method as in Example 19 was used to treat bromate in water, except that the material filled in the adsorption column in step (2) was replaced with an equal volume of commercial quaternized polystyrene-divinylbenzene copolymer spheres (D201). The experimental results were as follows: when the breakthrough point (BrO3 - The operation is stopped when the concentration is greater than 10ppb, and the treatment capacity of bromate water is only 40BV.

[0111] Embodiment 25

[0112] The same method as in Example 19 was used to treat bromate in water, except that the material filled in the adsorption column in step (2) was replaced with an equal volume of the propylene diamine resin in Example 1. The experimental results were as follows: when the breakthrough point (BrO3 - The process stops running when the concentration is greater than 10ppb, and the treatment capacity of bromate water is only 120BV.

[0113] The contents described in this specification are merely an enumeration of implementation forms of the inventive concept, and the protection scope of the present invention should not be regarded as being limited to the specific forms described in the embodiments.

Claims

1. An amine-functionalized resin-based nano-zero-valent ruthenium composite material, characterized in that: The matrix of the composite material is a polystyrene resin with a propylenediamine group, which is spherical, with a particle size distribution between 0.20 and 0.80 mm and a pore size distribution between 1 and 50 nm; holes are evenly distributed on the surface of the matrix, and zero-valent ruthenium nanoparticles are evenly distributed in the holes, the particle size of the zero-valent ruthenium particles is 2.0 to 30 nm, and the zero-valent ruthenium loading rate of the resin-based composite material is 0.5 to 5%.

2. The amine-functionalized resin-based nano-zero-valent ruthenium composite material according to claim 1, characterized in that: The zero-valent ruthenium loading rate of the resin-based composite material is 1.5 to 2.5%.

3. The method for preparing an amine-functionalized resin-based nano-zero-valent ruthenium composite material according to claim 1 or 2, characterized in that: The following steps are involved: a) adding chloromethylated polystyrene resin to N,N-dimethylformamide swelling agent, swelling treatment for 18 to 24 hours, then filtering off the swelling agent, solid-liquid separation to obtain swollen chloromethylated polystyrene resin, and washing with ethanol; then immersing the washed swollen resin in a mixed solution of propylene diamine and ethanol, heating in a water bath at 40 to 60° C. to carry out amino grafting reaction, filtering and washing with ethanol and water, and drying to obtain grafted propylene diamine resin; b) soaking the propylene diamine resin in a hydrochloric acid solution containing an appropriate amount of ruthenium salt for 20 to 30 hours and placing it in a shaking table at a speed of 100 to 200 rpm / min, filtering to obtain the propylene diamine resin impregnated with the loaded ruthenium ions, adding sodium borohydride solution dropwise to the propylene diamine resin loaded with ruthenium ions to reduce the ruthenium ions to zero-valent ruthenium, and then performing solid-liquid separation and washing with ultrapure water, and drying to obtain a resin-based nano-zero-valent ruthenium composite material.

4. The method for preparing an amine-functionalized resin-based nano-zero-valent ruthenium composite material according to claim 3, characterized in that: In step a), in the mixed solution of propylene diamine and ethanol, the volume concentration of propylene diamine is 20-80%; the mass volume ratio of the chloromethylated polystyrene resin to the mixed solution is 1:10-30, the unit of mass is g, and the unit of volume is mL.

5. The method for preparing an amine-functionalized resin-based nano-zero-valent ruthenium composite material according to claim 3, characterized in that: Step b) The concentration of the hydrochloric acid solution is 0.8-1.2 mol / L, and the ruthenium salt is at least one of ruthenium chloride, ruthenium nitrate, and ruthenium sulfate.

6. Application of an amine-functionalized resin-based nano-zero-valent ruthenium composite material in catalytic reduction of bromate in water as claimed in claim 1 or 2, characterized in that The following steps are involved: (1) adjusting the pH of the bromate-containing water body to 2.0 to 10.0, filtering, and obtaining a filtrate; (2) passing the filtrate obtained in step (1) through an adsorption tower filled with an amine-functionalized resin-based nano-zero-valent ruthenium composite material to obtain treated water; (3) When the water body treated by the adsorption tower reaches the breakthrough point, the operation is stopped, and the composite material is first desorbed with an alkaline solution, and then the composite material is rinsed with water to neutrality, and then reduced with a sodium borohydride solution to achieve regeneration of the composite material.

7. The use according to claim 6, characterized in that In step (1), BrO3 - The mass concentration of bromate in the water body is less than 100 mg / L, the mass concentration of other coexisting anions in the water body is less than 5000 times the mass concentration of bromate ions, and the anions include one or more of chloride ions, nitrate ions, carbonate ions, sulfate ions and phosphate ions; the concentration of coexisting organic acids in the water body is lower than 100 mg / L, and the organic acids are humic acid or fulvic acid.

8. The use according to claim 6, characterized in that In step (2), the temperature of the filtrate passing through the composite material is 5 to 40°C, preferably 20 to 30°C, and the water outlet flow rate of the adsorption tower is 2 to 5 BV / h.

9. The use according to claim 6, characterized in that In step (3), the breakthrough point is when the mass concentration of bromate in the effluent is greater than 0.01 mg / L, and the BrO3 - The alkali solution is a NaOH aqueous solution with a mass percentage concentration of 0.1 to 4%; when the alkali solution passes through the amino-functionalized resin-based nano-zero-valent ruthenium composite material, desorption is performed at a flow rate of 1 to 5 BV / h at 10 to 40°C, and its volume usage is 10 to 50 times the filling volume of the composite material in the adsorption tower.

10. The use according to claim 6, characterized in that In step (3), the sodium borohydride solution is a sodium borohydride aqueous solution with a mass percentage concentration of 0.5 to 3%; when the sodium borohydride solution passes through the resin-based zero-valent ruthenium composite material, it is regenerated at a temperature of 10 to 40° C. and a flow rate of 1 to 5 BV / h.

Citation Information

Cited By

  • Method for catalyzing isomerization of glucose into mannose by using supported metal catalyst

    CN120394086A